Tyazhelov Olexiy Alimovych - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The article is dedicated to the jubilee of the head of the biomechanics laboratory of the State Institution «Sytenko Institute of Spine and Joint Pathology» National Academy of Medical Sciences of Ukraine, Doctor of Medical Sciences, Professor Tyazhelov О.A.